Silenced Voices: Victims of the Holocaust
Ervin Schulhoff, String Quartet #1 played by Hawthorn String Quartet (16:58); Ervin Schulhoff, Concertino for Flute, played by Fen Wicksmith flute, Edwin Barker bass, Mark Ludwig viola (15:25); Vitezslava Karpalova, Dubmove Preluda Suite, opus 13 played by Virgina Eskin piano (7:35); Ervin Schulhoff, Sonata for Flute and Piano played by Fenwicksmith flute, Sally Pinkas piano (12:02) Gideon Klein,Duo for Violin & Cello played by Si-Jing Huang violin, Sito Knudsren cello (9:13)